2010
DOI: 10.4103/0253-7176.78506
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Nortriptyline and Fluvoxamine on Psychomotor Functions in Healthy Volunteers

Abstract: Background:Today, many antidepressants are available, but they often cause adverse effects, particularly psychomotor and cognitive. It leads to patient maladjustment and may impair psychomotor performance. Fluvoxamine is a newer antidepressant and hence the present study was planned to investigate its effect on psychomotor functions and compare with nortriptyline and record their adverse reactions.Materials and Methods:A total of 26 healthy volunteers were included in this double-blind, placebocontrolled, cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
3
4
1
2
Order By: Relevance
“…In our study, nortriptyline was significantly associated with headache, dizziness, constipation, drowsiness, weakness, and aggression, which seems to be in line with other studies 10–13,23,24. Khade et al reported that drowsiness, tiredness, and dullness were related to this drug, and Uher et al further reported that dry mouth, constipation, and weight gain were associated with nortriptyline 10,12…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, nortriptyline was significantly associated with headache, dizziness, constipation, drowsiness, weakness, and aggression, which seems to be in line with other studies 10–13,23,24. Khade et al reported that drowsiness, tiredness, and dullness were related to this drug, and Uher et al further reported that dry mouth, constipation, and weight gain were associated with nortriptyline 10,12…”
Section: Discussionsupporting
confidence: 92%
“…In our study fluoxetine was associated with nausea, similar to other studies 10–13,23,24. Meanwhile, Khade et al and Otsubo et al reported that fluvoxamine was associated with nausea and Uher et al reported that escitalopram was associated with insomnia, diarrhea, and yawning 10,12,24. In our study, fluoxetine was significantly associated with nausea, whereas Bhurghri et al reported that nortriptyline was significantly associated with nausea and headache 18.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Journal of Psychiatry and Brain Science 14 of 33 (e.g., immunomodulators, anticonvulsants, and ATD (such as bupropion and nortriptyline)) are being excluded given the potential impact of DA, a neurotransmitter important to motor functioning [67][68][69]. Subjects periodically taking medications that impact dopamine or other compounds that may impact motor functioning (e.g., antibiotics, antihistaminic, or antiemetic) will undergo a withholding period of four weeks prior to assessments.…”
Section: Medicationmentioning
confidence: 99%
“…3) Hand steadiness [11,12] The hand steadiness was tested on a steadiness tester. It is a device with a series of holes of varying sizes, a stylus and a digital counter.…”
Section: ) Reaction Timementioning
confidence: 99%